Given:
![y=-(2)/(9)x+3](https://img.qammunity.org/2023/formulas/mathematics/college/nrq9hxa8nkdcn5v2hwu0eaqbpa2dg20b4h.png)
The equation above is written in slope intercept form:
y = mx + b
To rewrite in standard form, use the standard form of linear equations below:
Ax + By = C
Thus, we have:
![y=-(2)/(9)x+3](https://img.qammunity.org/2023/formulas/mathematics/college/nrq9hxa8nkdcn5v2hwu0eaqbpa2dg20b4h.png)
Multiply through by 9 to eliminate the fraction:
![\begin{gathered} 9y=(-(2)/(9)x\ast9)+(3\ast9) \\ \\ 9y=-2x+27 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/iuhdy2xo6nydqqgdzj0xr3ord8fyr7lay0.png)
Add 2x to both sides:
![\begin{gathered} 2x\text{ + 9y = -2x + 2x + 27} \\ \\ 2x\text{ + 9y = 27} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/34y1sc7efzuv0xlv0o2jxeaoi7syu2g9xv.png)
Therefore, the equation in standard form is:
2x + 9y = 27
ANSWER:
D. 2x + 9y = 27